Determinants of FDI Inflows: The Case of Russian Regions - Mariev, Oleg Svyatoslavovich; Drapkin, Igor Mikhailovich; Chukavina, Kristina Vladimirovna; Rachinger, Heiko (Economy of Regions, 2016)
This paper empirically analyses the determinants of foreign direct investment inflows into the Russian regions. This problem has become highly relevant for the necessary modernization of the Russian economy after the recent economic slowdown and sharp decrease in budget revenues. The authors model foreign direct investment flows with the use of the gravity approach according to which investment flows are positively correlated with the size of the investor’s country as well as the size of the recipient region and are negatively correlated with the distance between investor and recipient. The empirical analysis is based on a constructed database consisting of the foreign direct investment flows from 179 investor countries into 78 Russian regions for the period 2006-2013. The authors apply the Poisson Pseudo Maximum Likelihood method and identify the following factors determining foreign direct investment inflows into the Russian economy: the gross domestic product of the investor’s country, the gross domestic product per capita in the recipient region, the distance from the investor to Moscow, the openness of the region, the economic situation in the region, the innovative capacity of the region and the foreign direct investment of the previous period. Interestingly, the distance from the recipient region to Moscow matters for the regions in the western part of Russia (relatively close to Moscow) but is not significant for the regions in the eastern part (remote regions).